Examining the Contextual Integration of Local Knowledge in Secondary Level Classroom Instruction - Bhattarai, Taranath (Chhahari छहारी, 2026)
This study examines the contextual integration of local knowledge in secondary-level classroom instruction, with particular attention to its role in promoting skill-oriented learning. Guided by a qualitative research approach, the study explores how local knowledge is incorporated into teaching–learning processes through task-based and context-responsive instructional practices. Data were collected through classroom observations and semi-structured interviews with selected participants. The analysis involved systematic immersion, thematic abstraction, synthesis, and interpretation to generate meaningful insights.Findings indicate that diverse forms of local knowledge derived from community practices, cultural traditions, and lived experiences are effectively integrated into classroom instruction to enhance student engagement and experiential learning. The study further reveals that task-based instructional strategies facilitate the practical application of curricular content, thereby supporting the development of transferable skills among secondary-level learners. The integration of local knowledge also contributes to creating meaningful learning environments that bridge formal education and students’ sociocultural contexts. The study recommends strengthening pedagogical practices, curricular flexibility, and institutional support to promote the systematic incorporation of local knowledge in secondary education for more relevant and contextually grounded learning experiences.